Engineering Technologist - Ricardo Gomez-Flores; Patricia Tamez-Guerra (Open Journal of Biological Sciences - Peertechz Publications, 2017)
Engineering must respond to innovation and change. The great innovations and technologies are generated in the centers and institutions of higher education, by modifying nature to meet our needs. Technology is a product of science and engineering and is associated with innovation, in which ideas become products or processes at the service of man. Engineering education must adapt to global change if it is to improve productivity and foster local and national economic development. Engineers of the next decade must have a technical or highly technological activity, and play leadership roles in academia, industry, and government. Areas of opportunity are in the generation of new products and processes related to nanotechnology, information technology, robotics and mechatronics, process automation, aerospace, food technology, bioengineering, biotechnology, etc. However, there are others related to transgenic food and nuclear technologies, which generate social controversy.